A ubiquitin-10 promoter-based vector set for fluorescent protein tagging facilitates temporal stability and native protein distribution in transient and stable expression studies - Grefen, Christopher; Schumacher, Karin (The plant journal, 2010)
Fluorescent tagging of proteins and confocal imaging techniques have become methods of choice in analysing the distributions and dynamic characteristics of proteins at the subcellular level. In common use are a number of strategies for transient expression that greatly reduce the preparation time in advance of imaging, but their applications are limited in success outside a few tractable species and tissues. We previously developed a simple method to transiently express fluorescently-tagged proteins in Arabidopsis root epidermis and root hairs. We describe here a set of Gateway-compatable vectors with fluorescent tags incorporating the ubiqutin-10 gene promoter (PUBQ10) of Arabidopsis that gives prolonged expression of the fluorescently-tagged proteins, both in tobacco and Arabidopsis tissues, after transient transformation, and is equally useful in generating stably transformed lines. As a proof of principle, we carried out transformations with fluorescent markers for the integral plasma membrane protein SYP121, a member of the SNARE family of vesicle-trafficking proteins, and for DHAR1, a cytosolic protein that facilitates the scavenging of reactive oxygen species. We also carried out transformations with SYP121 and its interacting partner, the KC1 K+ channel, to demonstrate the utility of the methods in bimolecular fluorescence complementation (BiFC). Transient transformations of Arabidopsis using Agrobacterium co-cultivation methods yielded expression in all epidermal cells, including root hairs and guard cells. Comparative studies showed that the PUBQ10 promoter gives similar levels of expression to that driven by the native SYP121 promoter, faithfully reproducing the characteristics of protein distributions at the subcellular level. Unlike the 35S-driven construct, expression under the PUBQ10 promoter remained elevated for periods in excess of 2 weeks after transient transformation. This toolbox of vectors and fluorescent tags promises significant advantages for the study of membrane dynamics and cellular development, as well as events associated with environmental stimuli in guard cells and nutrient acquisition in roots.